The effect of project-based learning model on students’ critical and creative thinking skills in the ecosystem concept - Fissilmi Khafah; Purwati Kuswarini Suprapto; Egi Nuryadin (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
Critical and creative thinking abilities are part of 21st century skills that have not been well utilized. One effort to improve these abilities can be through project-based learning (PjBL). This quantitative study aims to determine the effect of the PjBL model on students' critical thinking and creative thinking abilities on the ecosystem concept. This research used a quasi-experimental design with the matching posttest-only control group design and a population of all class The sample was determined using a purposive sampling technique with various considerations, selecting class X-1 as the experimental class and class X-2 as the control class. The research instrument used 15 questions for critical thinking skills and 12 questions for creative thinking. The collected data was then analyzed using the one-way ANOVA test. The results of the analysis show that the PjBL model has a significant effect on students' critical and creative thinking abilities on the ecosystem concept (P 0.000 < 0.05). Thus, the PjBL model can be used as an alternative learning to empower 21st century skills.